Reviving Traditional Food Knowledge Through Food Festivals. The Case of the Pink Asparagus Festival in Mezzago, Italy - Fontefrancesco, Michele F.; Zocchi, Dauro M. (Frontiers in Sustainable Food Systems, 2020)
The article investigates the link between food festivals and traditional food knowledge and explores the role played by tourist events in disseminating local agricultural and gastronomic knowledge. This article presents the ethnographic case of the Pink Asparagus Festival in Mezzago in Italy, analysing how the festival supported the continuation of crop production and its associated traditional knowledge in the village. In the face of a decline of asparagus production, the article highlights the role of the festival in fostering a revival of local food knowledge, which is also able to embrace modernisation, at the same time as maintaining a strong sense of the past and Mezzago's legacy. Thus, the article suggests that festivals are not just events aimed at commodifying local knowledge, but can be important tools to refresh and maintain local expertise, which is vital and pressing in the context of modern society.